Economic Growth and Environmental Quality Indicators - Sasikala, T.; Samad, Zakiya Abdul; Singh, N. Robindro; Sathya, J.; Gayathri, J. (International Journal of Energy Economics and Policy, 2025)
The economic growth of a nation is deeply intertwined with the availability and quality of its environmental resources. However, industrialisation, urbanisation, and agricultural expansion often pursued in the name of development have led to the overexploitation of natural assets, resulting in environmental degradation, climate change, and biodiversity loss. This paper examines the trade-off between economic growth, measured by Gross Domestic Product (GDP), and environmental quality indicators such as CO2 emissions, maximum, minimum, and mean temperatures, total greenhouse gas emissions, water stress levels, annual rainfall, and freshwater withdrawals by agriculture and industry. Drawing on data from 1990 to 2020, the study employs statistical analysis to investigate these relationships in the Indian context. The findings reveal a significant and positive correlation between GDP growth and environmental degradation, particularly in terms of rising emissions and temperature levels, increased water stress, and unsustainable freshwater use. These results underscore the need for policies that align economic development with environmental sustainability to safeguard long-term growth and resilience.